2x+6=3(x-2)

Simple and best practice solution for 2x+6=3(x-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+6=3(x-2) equation:


Simplifying
2x + 6 = 3(x + -2)

Reorder the terms:
6 + 2x = 3(x + -2)

Reorder the terms:
6 + 2x = 3(-2 + x)
6 + 2x = (-2 * 3 + x * 3)
6 + 2x = (-6 + 3x)

Solving
6 + 2x = -6 + 3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-3x' to each side of the equation.
6 + 2x + -3x = -6 + 3x + -3x

Combine like terms: 2x + -3x = -1x
6 + -1x = -6 + 3x + -3x

Combine like terms: 3x + -3x = 0
6 + -1x = -6 + 0
6 + -1x = -6

Add '-6' to each side of the equation.
6 + -6 + -1x = -6 + -6

Combine like terms: 6 + -6 = 0
0 + -1x = -6 + -6
-1x = -6 + -6

Combine like terms: -6 + -6 = -12
-1x = -12

Divide each side by '-1'.
x = 12

Simplifying
x = 12

See similar equations:

| 4/5x+2=-1/5x+5 | | 7x+18x-9=5(5x+5) | | 4x-7=9x-5 | | 15x+60=165 | | 13.24-2.7p=5.5p-0.7 | | 5x+3.0=2x+3.3 | | 14+56=28w | | .66y+v=x | | 13x+84=175 | | 5n+72=3n-36 | | n-3=-n+3 | | 8a-2a= | | 9w=6.3 | | y=2/3(11)+4 | | -15=(5q-10)-5q | | 2(w-4)=26 | | (5y-7)^-4/3((5y-7)-3) | | 5x-22=3x+16 | | -1.5(x-2.25)=-10.55 | | -3p+4=-9(5p-10)-2(-5-5p) | | 1/8(a+3)=1/4(9-a) | | (n+3)5=3(2n-1) | | 6x6/7 | | 2/3G=-5/2 | | (6/x-4)/(2x-3)=0 | | 10y-6=4y+8 | | 8h=26 | | 7-(2z-5)=6-3z | | 2/3y+v=x | | v-9=214 | | 16+8x=25+15+3 | | -13x-13=2x-46 |

Equations solver categories